The impact of interest rate, oil price, and Covid-19 cases on the Malaysian stock market returns during Covid-19 pandemic - Manggleshwary, Muniandy (2021)
This study aims to investigate the impact of interest rate, oil price and Covid-19 cases on stock market returns during Covid-19. In specific, this study is to determine relationship among Malaysia stock return (KLCI), interest rate (IR), oil price (POIL), daily Covid-19 confirmed cases and death cases during Covid-19. This study carried out on Malaysia country using daily data during Covid-19 pandemic extended from February 2020 to September 2021. The methods used to achieve this goal are ordinary least square regression analysis. The data are processed by using E-views software. By using regression analysis model the finding shows interest rate, oil price, and daily covid-19 confirmed cases has a positive relationship towards the stock return however only the oil price is significant during the current Covid-19 pandemic. The result found in covid-19 death case significantly has negative relationship with stock return. This suggests that oil price and daily covid-19 death cases can give impact to the Malaysian stock return.